Oleoylethanolamide treatment affects gut microbiota composition and the expression of intestinal cytokines in Peyer’s patches of mice - Di Paola, Monica; Bonechi, Elena; Provensi, Gustavo; Costa, Alessia; Clarke, Gerard; Ballerini, Clara; De Filippo, Carlotta; Passani, M. Beatrice (Scientific reports, 2018)
The lipid sensor oleoylethanolamide (OEA), an endogenous high-affinity agonist of peroxisome proliferator-activated receptor-α (PPAR-α) secreted in the proximal intestine, is endowed with several distinctive homeostatic properties, such as control of appetite, anti-inflammatory activity, stimulation of lipolysis and fatty acid oxidation. When administered exogenously, OEA has beneficial effects in several cognitive paradigms; therefore, in all respects, OEA can be considered a hormone of the gut-brain axis. Here we report an unexplored modulatory effect of OEA on the intestinal microbiota and on immune response. Our study shows for the first time that sub-chronic OEA administration to mice fed a normal chow pellet diet, changes the faecal microbiota profile, shifting the Firmicutes:Bacteroidetes ratio in favour of Bacteroidetes (in particular Bacteroides genus) and decreasing Firmicutes ( Lactobacillus ), and reduces intestinal cytokines expression by immune cells isolated from Peyer’s patches. Our results suggest that sub-chronic OEA treatment modulates gut microbiota composition towards a “lean-like phenotype”, and polarises gut-specific immune responses mimicking the effect of a diet low in fat and high in polysaccharides content.